La communauté anglophone des Îles prend des mesures afin de mitiger les effets de la pandémie du COVID-19 - Council for Anglophone Magdalen Islanders (CAMI) (2020)

The English-speaking Community of the Magdalen Islands Takes Action to Mitigate the Effects of the COVID-19 Pandemic - Council for Anglophone Magdalen Islanders (CAMI) (2020)

Needs Assessment & Identification of Opportunities : Fishery Assistance Report - Anderson, Annie-May (Coasters Association, 2004)
Funds were received from the Department of Fisheries and Oceans to assess the needs and identify the opportunities of the fishers and plant workers affected by the closure of the crab in Zone 13, and the closure of the cod in the Municipality of Bonne Esperance and Blanc Sablon. With the moratorium imposed on the cod and the closure of the snow crab fishery, the fishers and plant workers were consulted to obtain their views, which will provide a working tool for long term planning for the Coasters Association, Fishermen’s Committees, Municipalities, and Government officials. The first phase of the fishery project began on January 12th, 2004, and finished on May 29th, 2004. The second phase began on May 31st, 2004, and finished on October 1st, 2004. The objective of the project was to identify the issues, opportunities, and the individual needs ofthe fishers and plant workers affected by the closure of the crab in Zone 13, and inshore fishers affected by the closure of the cod in the Municipality of Bonne Esperance and Blanc Sablon.

A Report on the Quebec Fishing Community Adjustment Measures (QFCAM) Project - Blanche, Diana (Coasters Association, 2003)
The following report is a compilation of information pertaining to the activities under taken by the participants of the Fishery Restructuring Program.

Wildlife Species on the Magdalen Islands - Clark, Rachelle (1995)

A Day in the Life of a Fisherman

Down the Lane to Wallie's : A Story About Life on the Magdalen Islands - Clarke-Selander, Dorothy